Free Antiradical Activity Test of Endophytic Fungi Isolates of Kasumba Turate (Carthamus tinctorius (L) Leaves from Galesong Takalar with KLT-Autography Method - Sari, Dewi Mustika; Kosman, Rachmat; Rusli, Rusli (Journal Microbiology Science, 2024)
The kasumba turate plant (Carthamus tinctorius (L.) has the potential as a free antiradical. Free antiradical compounds in kasumba turate plants come from secondary metabolites produced by endophytic compounds known as endophytic fungi. Kasumba turate contains phenolic compounds and carotenoids that have antioxidant activity. This study aims to obtain isolates of endophytic fungi in kasumba turate (Carthamus tinctorius (L.) plants that can act as free antiradicals by KLT-Autography method. Five isolates IFDK 01, IFDK 02, IFDK 03, IFDK 04, and IFDK 05 were obtained. After testing the antioxidant activity of endophytic fungal isolates, two isolates were obtained that gave the best antioxidant activity, namely isolates IFDK 03 and IFDK 04. The results of KLT-Autography testing by spraying DPPH isolates IFDK 03 and IFDK 04 have the potential as free antiradicals showing yellow spots on a purple background having an Rf1 value, IFDK 03 isolate 0.94 and Rf2 0.55 and Rf1 value, IFDK 04 isolate 0.76 and Rf2 0.43